Preliminary study on tourist satisfaction, destination image, and destination loyalty to Terengganu, Malaysia - Zazalı, Zarıth Shamıhah; Ahmad, Siti Yuliandi (Korint Yayincilik, 2024)
Tourism is one of the world's most essential and fastest-growing businesses, the primary driver of Malaysia's economy. Terengganu is a prime example of a Malaysian state with many tourist attractions, ranging from its stunning islands and sandy shores to its rich cultural legacy and outdoor pursuits. Nonetheless, the data on tourist arrivals in Terengganu indicates that the number of visitors to Terengganu will consistently decline from 2019 until 2023. Therefore, this research aims to assess the relationships among tourist satisfaction, destination image, and destination loyalty of tourists to Terengganu. This study employed a quantitative research design with a convenience sampling technique. An online survey was distributed to a total of 100 respondents. IBM SPSS version 27 was used to analyse the data using descriptive, Pearson, and Multiple Regression analysis. The descriptive analysis for research objective one showed that the mean level for independent variables of Tourist Satisfaction and Destination Image is equal to or higher than (M=4.4240) and (M=4.1630), which is very good. Thus, there is a favourable correlation between Terengganu's destination image and destination loyalty. While this is happening, the research's implications may help future scholars and Terengganu authorities ensure that visitors are happy and inclined to return while enhancing the province's tourism industry.